DAMPAK PENCEMARAN LINGKUNGAN AKIBAT LIMBAH DAN UPAYA PENANGGULANGANNYA DI KOTA DENPASAR - I Made Ari Permadi; R. A. Retno Murni (Kertha Negara : Journal Ilmu Hukum, 2013)
Environment is very important in the human life cycle. In modern times problemsarise regarding the environment. In this paper the issue raised is the impact ofenvironmental pollution caused by sewage and waste as well as the government's effortsto prevent environmental pollution.To these problems occurs line with technologicaldevelopments who without pay attention to environment. Environmental pollution hasan impact on health, aesthetics, economic losses, and disruption of natural ecosystems.The method used in this paper is a juridical-empirical, theoretical approach using factsand laws. The conclusion of these problems is the lack of awareness on the part ofindustry employers and the community to protect the environment from pollution andwaste bins will berdampaknya the destruction of natural ecosystems and reducedenvironmental quality standards.